Electrical conditioning of adipose‐derived stem cells in a multi‐chamber culture platform. Issue 7 (17th February 2014) - Pavesi, A.; Soncini, M.; Zamperone, A.; Pietronave, S.; Medico, E.; Redaelli, A.; Prat, M.; Fiore, G. B.
ABSTRACT In tissue engineering, several factors play key roles in providing adequate stimuli for cells differentiation, in particular biochemical and physical stimuli, which try to mimic the physiological microenvironments. Since electrical stimuli are important in the developing heart, we have developed an easy‐to‐use, cost‐effective cell culture platform, able to provide controlled electrical stimulation aimed at investigating the influence of the electric field in the stem cell differentiation process. This bioreactor consists of an electrical stimulator and 12 independent, petri‐like culture chambers and a 3‐D computational model was used to characterize the distribution and the intensity of the electric field generated in the cell culture volume. We explored the effects of monophasic and biphasic square wave pulse stimulation on a mouse adipose‐derived stem cell line (m17.ASC) comparing cell viability, proliferation, protein, and gene expression. Both monophasic (8 V, 2 ms, 1 Hz) and biphasic (+4 V, 1 ms and −4 V, 1 ms; 1 Hz) stimulation were compatible with cell survival and proliferation. Biphasic stimulation induced the expression of Connexin 43, which was found to localize also at the cell membrane, which is its recognized functional mediating intercellular electrical coupling. Electrically stimulated cells showed an induced transcriptional profile more closely related to that of neonatal cadiomyocytes, particularly for biphasic stimulation. The developed platform thus allowed to set‐up precise conditions to drive adult stem cells toward a myocardial phenotype solely by physical stimuli, in the absence of exogenously added expensive bioactive molecules, and can thus represent a valuable tool for translational applications for heart tissue engineering and regeneration. Biotechnol. Bioeng. 2014;111: 1452–1463. © 2014 Wiley Periodicals, Inc.